Exploring the Relationship Between Honesty-Humility, the Big Five, and Liberal Values in Swedish Students - Petri J. Kajonius (Europe's Journal of Psychology, 2014)
Previous research on the Five-Factor model (Big Five) reports a relationship between personality traits and liberal values, and the trait Agreeableness has demonstrated the strongest relationship. The HEXACO model offers a complement to the Five-factor model with an additional sixth trait of Honesty-Humility. Previous research on the Honesty-Humility trait has reported mixed results with liberal values, and this study set out to resolve this. The work presented here explored the relationship between the Honesty-Humility trait on facet-level (Sincerity, Fairness, Greed-avoidance and Modesty) and liberal values (equality for women, minorities, and socio-economical groups). Data from Swedish students (N = 202), known for their individualistic and liberal mindset, were sampled. There was an overall positive correlation between Honesty-Humility and the strength of liberal values (r = .36), and Honesty-Humility predicted liberal values beyond Agreeableness. We discuss these results in terms of the significance of traits and values in a culture that promotes both individualism and equality.